Dessiner à l’Université ? Esquisse d’un cheminement - Lou Herrmann (EchoGéo)
Can drawing be an academic writing? Does it participate in the diffusion and construction of scientific knowledge? Like a thick history that links geography and drawing, this text hypothesizes that it does. Thanks to my drawing practice in an academic environment, I explore its own attributes and sketch the potentialities of its mobilization in social science research. It proves to be, a formidable tool for translation, synthesis, investigation or abstraction.